-4x + 3y = 9
4x + 3y = 7 y = [(-4)/3] x + 7/3
3y = 4x + 9 -4x + 3y = 9 is the standard form
You need to organise your question properly. 3x+2y=4 4x + 3y= 7? Is 4 4x = 44x or 4-4x or 4+4x How can there be 2 equal signs in 1 equation?
4x + 3y=9 x=0 y=3
4x+3y = 12 3y = -4x+12 y = -4/3x+4
4x+3y = 6 3y = -4x+6 y = -4/3x+2 in slope intercept form
x = 3 and y = 0
To solve for 2 unknown variables you need 2 independent equations. You have only 1.
4x + 3y = 6y 4x = 3y 4/3 x = y The slope is 4/3 and the y intercept is 0.
6x plus 4y
6x plus 3y minus 2x plus 5y equals 4x plus 8y.
4x+3y = 3 3y = -4x+3 y = -4/3x+1 in slope intercept form
-3y + z = 12
The given equation: =3x-4x plus 9xy-12y =3x-4x+9xy-12y =-x+9xy-12y =-x+3y(3y-4) Answer.
There are two simultaneous equations, so to solve for y, eliminate x: 1) 2x + 3y = 3 2) 4x - 3y = 9 Multiply equation (1) by 2 giving: 1) 4x + 6y = 6 2) 4x - 3y = 9 Next, subtract equation (2) from equation (1), giving: (4x - 4x) + (6y - -3y) = 6 - 9 → 9y = -3 → y = -1/3
4x = -3y+8 3y = -4x+8 y = -4/3x+8/3 So the slope is -4/3 or -1 and a 1/3
They are parallel lines.
6x - 4y
Normally, this is a difficult form of the equation to deal with. To change it into a more familiar form, we can do this: 4x + 3y = 0 3y = -4x y = (-4/3)x